Home Support and Exclusive Breastfeeding; Perspectives of Household Level Actors - Larri , J. (University Of Ghana, 2018)
Background: Exclusive breastfeeding (EBF) has been established as a healthy means of feeding an infant. It is recommended for the first six months of a child’s life. This study sought to estimate exclusive breastfeeding rate and explore its household level enablers and barriers in the Ga South Municipality. Methods: Across-sectional study using both quantitative and qualitative methods were employed. Structured questionnaires were administered to mothers for the quantitative aspect while in-depth interviews were conducted for spouses and grandmothers selected for the study. The data collection was within the period of June and July 2018. A Multi-stage sampling method was employed in the selection of facilities and participants involved in the study for the quantitative aspect, maximum variation sampling was employed to identify key spouses and grandmothers to be interviewed for the qualitative aspect. Basic descriptive statistics were run (frequencies and percentages) as well as bivariate and multivariable e analysis. Data was analyzed using Stata and Nvivo analysis software Results: All of the mothers agreed that breastfeeding was a good practice. Despite the fact that early initiation of breastfeeding within the first hour of birth was high (64.9%), the rate of EBF was less than half of it (30.8%). A significant relationship was found between the initiation of breastfeeding and the practice of EBF (p value=0.035). Mothers who received tertiary education were 2 times more likely to practice EBF than their counterparts who received basic education (AOR=1.713, 95% CI, 0.920-3.188). The home support for EBF from the household level actors showed a moderate acceptance to EBF being a good practice, some of the respondents expressed concerns of hygiene on the side of the mothers and also a quest to quench the thirst of the babies. Almost all the respondents that there was a comfortable home environment to support EBF. Almost all of the participants were willing to accept home visits by trained health professionals to support EBF. Conclusion: The proportion of mothers who practiced EBF was found to be much lower as compared to the national figure of 52%.Even though initiation of breastfeeding within the first hour was a bit higher the practice of EBF was lower in the municipality. Family support was found to be significantly associated to practice exclusive breastfeeding.
MPH.
Keywords: Exclusive Breastfeeding; infant; Household Level Actors